Penerapan Algoritma Deteksi Tepi Canny Menggunakan Python Dan Opencv - Saluky; Yoni Marine (Primakara University, 2023)
Abstract: Object detection is one step in object recognition in the field of computer vision. The edges of the image characterize the boundaries that distinguish it from other objects and are therefore a very important problem in image processing. Accurate Image Edge Detection can significantly reduce the amount of data and filter out useless information while retaining important structural properties in the image. Since edge detection is at the forefront of image processing for object detection, it is very important to have a good understanding of edge detection algorithms. In this study, applying canny edge detection using python and OpenCV and also compared with other image processing methods. The result is that Canny edge detection has a better performance compared to other algorithms such as LoG (Laplacian of Gaussian), Robert, Prewitt and Sobel.